2000
DOI: 10.1116/1.582305
|View full text |Cite
|
Sign up to set email alerts
|

Compositional heterogeneity in ceria-based mixed oxides observed by x-ray photoelectron spectroscopy

Abstract: Articles you may be interested inPt metal-CeO 2 interaction: Direct observation of redox coupling between Pt 0 / Pt 2 + / Pt 4 + and Ce 4 + / Ce 3 + states in Ce 0.98 Pt 0.02 O 2 − δ catalyst by a combined electrochemical and x-ray photoelectron spectroscopy study Stability of cerium oxide on silicon studied by x-ray photoelectron spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Surface compositions in cerium and zirconium were determined by peak integration of Ce 3d and Zr 3p for the each mixed-oxide FSP series and four CP solids (SI). We found that for all solids, the estimated binding energies (181.85 +/-0.05 for Zr 3d and 882.2 +/-0.2 for Ce 3d ) are similar to values reported in the literature[57]…”
supporting
confidence: 85%
“…Surface compositions in cerium and zirconium were determined by peak integration of Ce 3d and Zr 3p for the each mixed-oxide FSP series and four CP solids (SI). We found that for all solids, the estimated binding energies (181.85 +/-0.05 for Zr 3d and 882.2 +/-0.2 for Ce 3d ) are similar to values reported in the literature[57]…”
supporting
confidence: 85%